Magdalena : river of dreams - Davis, Wade (Alfred A. Knopf, 2020)
"The award winning writer, photographer, filmmaker, and ethnographer--a longtime Explorer-in-Residence at the National Geographic Society--recounts an enthralling journey down Colombia's Magdalena River that illuminates the country's rebirth after decades of political violence, drug cartels, and guerrilla warfare"--